ETIKA MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA UNIVERSITAS MALIKUSSALEH TERHADAP DOSEN DITINJAU DARI KEMAMPUAN BERFIKIR KRITIS - Fauzan, Fauzan (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2020)
This research aims to examine the correlation between critical thinking and ethics and the contribution of critical thinking to ethics. This research is a field research (field research) with a quantitative approach. Therefore the sample of this study amounted to 61 people. Data collection was carried out by visiting subjects in class during study hours by asking the head of the study program for permission first. Based on the results of the analysis of research data, it can be concluded in this study that they are as follows: 1. Students' critical thinking skills in the 2019-2020 school year are categorized as quite good, this is evidenced by the mean results of 57.87 which are in the "Good Enough" category. ". 2. Student ethics for the 2019-2020 school year are classified as good, this is evidenced by the mean result of 83.21 which is in the "Good" category. 3. There is a positive relationship between critical thinking skills and student ethics for the 2019-2020 academic year as evidenced by the value of r-count > r-table, which is 0.331 > 0.227 at the 5% significant level. With a significant value = 0.009, 0.05, the hypothesis Ha is declared "accepted". In this case the ability to think critically with ethics contributed 10.9% while the remaining 89.1% was determined by other variables.